HUMAN RESOURCE MANAGEMENT AND STRATEGY EFFORTS TO IMPROVE THE EFFECTIVE USE OF INDONESIA'S NATURAL RESOURCES - Jamadi; Prabawani , Bulan; Widiartanto; Shinta Dewi, Reni (RADJA PUBLIKA, 2023)
This study discusses human resource management strategies to improve the efficiency of natural resource management in Indonesia. We obtained data electronically from several data sources, books, and other scientific papers, all of which discuss HR and natural resources. The data can answer our problem of accepting the data close to the phenomenology of conclusions through various investments, the point of which is to get valid answers. Based on the existing research, we can conclude, among other things, that strengthening human resources in the field of technology can provide extraordinary efficiency to class data for all Indonesian natural resources such as water, air, energy, food, and all existing risks that can be adequately managed when human resources correctly care for sound management of human resources for good. These findings are expected to help increase similar studies in the future.